Comprehensive investigation of flexural buckling of compound cantilever beams or columns subjected to concentrated lateral or axial compressive load at free end - Rao, K. Durga; Karthikeyan, T.V.; Hussain, M. Manzoor; Rao, G. Venkateswara (Journal of Structural Engineering, 2025)
The flexural buckling behavior of cantilever compound beams or columns, made up of two different materials, in the two equal length segments, is investigated in this paper. No specific materials are chosen in this study, so as to make the study more general, but the material in the first segment, from the clamped end to the midpoint, is chosen to have a higher Young’s modulus, when compared to the same for the remaining segment. In both the segments, the area moment of inertia of the cross-section is taken as constant. The production aspects of welding of two dissimilar materials and the industrial application of the compound beams or columns to achieve the efficient and cost effective designs are presented. The versatile finite element method, with the different ratios of the Young’s modulii, is used to obtain the numerical results, in terms of the lateral deflection, slope the buckling load parameters and the mode shapes of the cantilever compound beams and columns, which are the important design inputs for the efficient structural design. The present investigation reveals some interesting trends, based on the numerical results obtained, hitherto not reported explicitly.